The Effect Of Project Based Learning On Students' Learning Outcomes In The Respiratory System Material Of Grade Xi Sma N 1 Rantau Utara - Nuraini, Witma Novita Atnur, Rizki Lestari (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study aims to analyze the effect of the Project-Based Learning (PjBL) model on student learning outcomes in the respiratory system material in class XI of SMA N 1 Rantau Utara. The research method used is quantitative with a quasi-experimental design, using a pretest-posttest control group design. The research sample consisted of two classes selected using a purposive sampling technique, namely one class as an experimental group using the PjBL model and one class as a control group using conventional learning methods. Learning outcome data were obtained through pretest and posttest, then analyzed using normality tests, homogeneity tests, and t-tests to determine differences in learning outcomes between the two groups. The results showed that before being given treatment, there was no significant difference between the pretest scores of the two groups, with an average pretest score of the experimental group of 65.12 and the control group of 64.85.